2021
DOI: 10.2147/cmar.s330357
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis Value of microRNA-3677-3p in Lung Adenocarcinoma and Its Regulatory Effect on Tumor Progression

Abstract: Purpose Lung adenocarcinomas (LUAD) was the most common subtype of lung cancer, and may result in a poor prognosis. This study was designed to explore the role of miR-3677-3p in LUAD and discuss in what way it functions in LUAD. Materials and Methods We used RT-qPCR method to detect the expression levels of miR-3677-3p in 105 pairs of LUAD tissues and noncancerous tissues, as also as in LUAD cells. We used χ 2 test to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Yoshikawa et al 15 intraperitoneally injected synthetic miR-214 into mice with canine angiosarcoma and observed that it produced antitumor effects by inducing apoptosis and inhibiting cell proliferation. In addition, miRNA expression has been shown to affect the occurrence, development, and prognosis of various malignancies, including lung cancer, 16 prostate cancer, 17 and liver cancer. 18 Since the critical role of miRNAs in cancer has been demonstrated, gene therapy based on miRNA has attracted considerable attention.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshikawa et al 15 intraperitoneally injected synthetic miR-214 into mice with canine angiosarcoma and observed that it produced antitumor effects by inducing apoptosis and inhibiting cell proliferation. In addition, miRNA expression has been shown to affect the occurrence, development, and prognosis of various malignancies, including lung cancer, 16 prostate cancer, 17 and liver cancer. 18 Since the critical role of miRNAs in cancer has been demonstrated, gene therapy based on miRNA has attracted considerable attention.…”
Section: Discussionmentioning
confidence: 99%